If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-10f-10=-10f+8-2f
We move all terms to the left:
-10f-10-(-10f+8-2f)=0
We add all the numbers together, and all the variables
-10f-(-12f+8)-10=0
We get rid of parentheses
-10f+12f-8-10=0
We add all the numbers together, and all the variables
2f-18=0
We move all terms containing f to the left, all other terms to the right
2f=18
f=18/2
f=9
| M+1/3(m+21)+m+8=71 | | 3c-2c=4-9 | | 5=d/3− 3 | | 36y−98+53y=92y+73 | | 12+y=81 | | i+5(I-3)-5(-6-4i)=15 | | 1.2x+4.8=0.6-1.8 | | 8u=42 | | 1/2+2m=m | | 18-2y=9 | | 3.5/7=7/x | | 73=9n+19 | | 6(6x6)=6(36) | | 4+k/12=5 | | 3(x+3)-5=7x+20 | | 37=52+z | | 0.5x-5=-1.5x+4 | | s/5=16 | | 9=q+318 | | -16/15=n/15 | | 3n/4+7n-5=-2.5 | | -6-6c=-10c+6 | | –4w+–11=9 | | 44=4(s+8) | | 6+25x+18x-3+44=180 | | 3(x−6)=2x−1 | | 4(t-3)t=13 | | –3s+7=–2s | | -10=-4+n | | -0.4k-6=1.2 | | 6p+5=7p-5 | | -2/5x=-17 |